Muscari erdalii (Asparagaceae, Scilloideae), a new species from Southern Turkey - Demirci, Serpil; Özhatay, Neriman; Koçyiğit, Mine (Phytotaxa, 2013)
Muscari erdalii is described as a new species from Mersin, Southern Turkey. A description, photographs and identification key to the subgenus Leopoldia for Turkish species are given. The morphological differences between the new species and related taxa (M. tenuiflorum Tausch, M. babachii Eker & Koyuncu) are also presented. Also the karyomorphology of M. erdalii, M. tenuiflorum and M. babachii is presented and discussed. The chromosome number of the new species is 2n = 18.